Characterisation, Synthesis, and Antimicrobial Activities of Silver Nanoparticles Formed via Green Synthesis Approach using Aqueous Extract derived from the Bark of Mangifera indica: A Sustainable Resource - Tailor, Shalini; Malik, Ayushi; Gaur, R K; Marwal, Avinash (Defence Life Science Journal, 2025)
Many research opportunities have arisen as a result of the green synthesis method for nanoparticle creation and the rapid development and breakthroughs in nanotechnology. This study covers the one-step synthesis of silver nanoparticles (SNPs) from Mangifera indica bark aqueous extracts. Bark extract is combined with AgNO3 to perform green synthesis of SNP. The synthesised SNPs were characterised by a color change from light yellow to deep brown, as well as UV-VIS spectrophotometry in the 300-700 nm area. Further characterisations were carried out using Fourier transform infrared spectroscopy (FTIR) and X-Ray Diffraction (XRD) studies, followed by Scanning Electron Microscopy (SEM) and Energy-Dispersive X-ray spectroscopy (EDX) analysis. Phytochemical examination of crude bark extract revealed the existence of secondary metabolites alkaloids, flavonoids, phenolics, tannins, and saponins but no glycosides and starch were present. The antimicrobial activity (AMA) of Bark SNP (BSNP) towards gram-positive bacteria [Staphylococcus Aureus (SA) & Streptococcus Pyogenes (SP)], gram-negative bacteria [E. coli (EC) & Pseudomonas aeruginosa (PA)], and Candida species were determined using the disc diffusion technique. A single-factor ANOVA was used for performing the statistical analysis, and p-values < 0.05 designated statistical significance. The green synthesised SNPs were spherical and crystal size ranged between 10 and 12 nm on average. In UV-vis spectroscopy, the absorption spectra peaked at 460 nm. It was discovered that the SNPs’ antibacterial activity was stronger than their antifungal activities. Compared to commercial medicines, the BSNP exhibits a reasonable inhibitory effect. The purpose of the current study was to build a new, affordable, ecologically safe process for a plant-mediated green approach for SNP synthesis and evaluate its antimicrobial activity for sustainable resources.